SOSIALISASI STANDAR PEMERIKSAAN LAPORAN KEUANGAN BLUD RUMAH SAKIT UMUM DAERAH BERBASIS STANDAR AKUNTANSI PEMERINTAHAN - Andi Faisal; Adriansyah Adriansyah; Fina Ruzika Zaimar; Nurlina Nurlina (Universitas Ichsan Sidenreng Rappang, 2026)
This community service activity aimed to enhance the understanding of financial and accounting staff at Lapalaloi Regional General Hospital (RSUD), Maros Regency, regarding financial statement audit standards for Regional Public Service Agencies (BLUD) based on Government Accounting Standards (SAP). The activity was conducted through a structured socialization method involving lectures, interactive discussions, and case study analysis in January 2026. Results demonstrated a significant improvement in participants' understanding, with an average pre-test to post-test score increase of 47.7%. The highest improvement was recorded in the mechanism of BLUD financial statement auditing (52.1%) and external audit preparation procedures (51.2%). Three major technical challenges were also identified through discussion sessions: fixed asset recognition, preparation of Notes to Financial Statements (CaLK), and audit documentation standardization. This activity contributed to strengthening the institutional capacity of RSUD Lapalaloi in preparing accountable, audit-ready financial statements in accordance with PPK-BLUD regulations.